Co-implementation of tillage and precision nutrient management practices on crop yield of kharif maize (Zea mays) - NAIK, BANAVATH MAHESH; KUMAR, MRITUNJAY; M, KARTHIKA; SINGH, S K; KUMAR, NAVNIT; RAY, NAWAL KISHOR (The Indian Journal of Agricultural Sciences, 2023)
Our accustomed agricultural practices of tilling the soil continuously and excessive fertilizer applications caused not only a decrease in organic carbon content and soil degradation but also disturbed environmental harmony. With this backdrop, current study was carried out during rainy (kharif) seasons of 2018 and 2019 at the research farm of Trihut College of Agriculture, Dholi, Pusa, Bihar to evaluate the effect of different tillage and nutrient management practices on maize (Zea mays L.). The experiment was laid out in split-plot design with tillage as the main plot and nutrient management as the sub-plot. The results showed significantly superior maize grain yield in PB (6.1, 6.2 mg/ ha) and 60% RDN+GSGN (6.0, 5.9 mg/ha) over CT (4.9, 5.0 mg/ha) and RDF (5.1, 5.4 mg/ha) during 2018 and 2019. Similar trend was followed in stover yield, net returns and B:C ratio. Among path analysis, harvest index and no of grains/cob observed largest direct path coefficient of yield attributes to determine the maize grain yield and stover yield respectively. The results suggest that the adoption of conservation tillage and precise nutrient management practices will help in the realization of better yield with maximum profit by way of reducing the input capital apart from improving soil health thereby sustaining natural resources for future generations.